EFFECTOF EXTRUSION CONDITIONS ON AFLATOXIN CONTENT OF CORN–PEANUT FLAKES - Molla, Aynadis; Zegeye, Adamu (Zede Journal of Ethiopian Engineers and Architects, 2023)
The study was conducted to evaluate the influence of extrusion operating conditions on the reduction of total and individual aflatoxins (B1 and B2) in corn-peanut flakes. Aflatoxin - contaminated corn and peanut were converted into flour separately and mixed in a proportion of 70 % corn and 30 % fully defattened peanut flour (FDPF). Corn-peanut extrudates and flakes were then produced at various combinations of feed moisture contents (17% and 21%,) barrel temperatures (140°C, 160°C and 180°C) and screw speeds (150 rpm,200 rpm and 250 rpm)in a double screw extruder under factorial design. The process parameters were recorded during the experiment. The total and individual aflatoxins were measured using a high-performance liquid chromatography (HPLC) before and after extrusion. The collected data were then subjected to analysis of variance by SPSS statistical software. The results showed that the total aflatoxin was cut by more than 95% (from 583 ppb to 30 ppb) at constant (150) rpm while other parameters varying. Similarly, aflatoxinsB1 and B2 decreased by nearly 93.8% (240 to 15 ppm) and 83.5% (23 to 3.8 ppb), respectively (P<0.05) at different combinations. Of all the conditions, 17 %, 160 0C and 200 rpm reduced both B1 (240 to 15ppb) and B2 (23 to 7.5 ppb) at the same time. Corn and peanut are crops partly used for making Injera and edible oil in Ethiopia, respectively. Corn ranks next to Teff in area coverage and first in total production in Ethiopia. The inclusion of peanut in the production of corn flakes improves the protein content. Corn and peanut are excellent